2020
DOI: 10.1001/jamaoto.2020.0526
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Burning Mouth Syndrome and the Development of Depression, Anxiety, Dementia, and Parkinson Disease

Abstract: Burning mouth syndrome is a chronic oral pain disorder that is characterized by a generalized or localized burning sensation without the presence of any specific mucosal lesions. It remains unclear, however, whether burning mouth syndrome is associated with the development of psychoneurological conditions among patients with the syndrome. OBJECTIVE To evaluate the risk of developing psychoneurological conditions, including depression, anxiety, dementia, and Parkinson disease, in patients with burning mouth syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 45 publications
2
47
0
4
Order By: Relevance
“…Patients affected by NCP are considered to be at high risk to develop a cognitive decline, especially in the domains of attention, working memory, and executive functions (Moriarty et al, 2011;Moriarty and Finn, 2014), which leads to the poor quality of life, difficulty in adherence to medications, increasing the risk of mortality, and health resource utilization (O'Connor, 2009;Colloca et al, 2017). Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020;Pereira et al, 2020) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al (2020), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ∼10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients affected by NCP are considered to be at high risk to develop a cognitive decline, especially in the domains of attention, working memory, and executive functions (Moriarty et al, 2011;Moriarty and Finn, 2014), which leads to the poor quality of life, difficulty in adherence to medications, increasing the risk of mortality, and health resource utilization (O'Connor, 2009;Colloca et al, 2017). Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020;Pereira et al, 2020) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al (2020), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ∼10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020 ; Pereira et al, 2020 ) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al ( 2020 ), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ~10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020 ). Instead, case-control or prospective studies have never been carried out with an aim to establish if patients with BMS may suffer of CI as well as mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…94 96 Kim et al reported no correlation between patients with BMS and the risk of developing Parkinson disease. 97 Besides, the evidence on the association of Parkinson disease and BMS were exhibited in deficiency of habitual blink reflex in both groups. 82,83,98 The level of dopamine increased during the night sleep of Parkinson’s disease patient which improved their dopaminergic function during the sleep.…”
Section: Aetiopathogenesismentioning
confidence: 89%
“…BMS is a chronic disorder characterized by burning pain in the mouth in the absence of any visible oral or medical cause. Most patients with BMS are accompanied by anxiety, depression, and other mental disorders[ 11 ], which seriously affect the sleep and quality of life[ 12 ]. In recent years, the incidence of BMS has been increasing year by year, however, due to the complex etiology and pathogenesis, there is still no specific and effective treatment[ 3 ].…”
Section: Discussionmentioning
confidence: 99%